Gut response to the dietary supplementation with sodium butyrate in broiler chickens: morphology and microbiota composition and predictive functional groups - Giulia Zardinoni; Almudena Huerta; Marija Boskovic Cabrol; Angela Trocino; Elisa Fonsatti; Cristina Ballarin; Martina Bortoletti; Marco Birolo; Francesco Bordignon; Piergiorgio Stevanato; Daniel Julian; Gerolamo Xiccato (Italian Journal of Animal Science)
This study investigated the effects of Na-butyrate supplementation (0 vs. 150 vs. 300 mg/kg) and the dietary fat level (7.7% vs. 6.7% in the grower diet; 8.9% vs. 7.7% in the finisher diet) in 900 broiler chickens of both sexes, out of which 108 were used to evaluate gut morphology and immune response on jejunum tissues at 14, 28, and 40 days of age, and caecal microbiota composition according to 16S rRNA gene multi-amplicon sequencing and the predictive functional bacteria groups at 40 d of age. Villi height and crypts depth changed only according to the age of chickens. Microbiota analysis revealed Firmicutes as the dominant phylum, with sex-related differences in microbial diversity indices (Simpson index, p < .05). The Na-butyrate dietary supplementation and dietary fat level affected the abundance of specific bacterial genera related with short fatty acids production, without changes in the bacterial metabolic pathways. Under the good health conditions of chickens in the present trial, Na-butyrate supplementation and the dietary fat level did not modify the overall gut equilibrium of broiler chickens.